Pengaruh Good Governance dan Kompetensi Sumber Daya Manusia pada Kualitas Laporan Keuangan di Kota Denpasar - Anggreni, Ni Made Mei; Widanaputra, A. A. G. P.; Asri Dwija Putri, I G. A. M. (E-Jurnal Akuntansi; Vol 22 No 1 (2018)DO - 10.24843/EJA.2018.v22.i01.p14, 2018)
The purpose of this study to determine the effect of good governance and human resource competence on the quality of financial statements in the government of Denpasar. This research was conducted at Organization of Regional Device (OPD) Denpasar City. Determination of sample by using nonprobability sampling that is by approach of purposive sampling and get sample counted 32 OPD. Methods of data collection in this study by using questionnaires given to the head of the financial sub-department, treasurer and the most senior financial officers in each OPD. Data analysis technique used is multiple linear regression analysis. The results of this study illustrates that good governance and competence of human resources affect the quality of financial statements of the government of Denpasar. It means the better implementation of good governance is also increasing the quality of financial statements and the higher the competence of human resources is also increasing the quality of financial statements Keywords: Financial report, good governance, HR